An important role of an inducible RNA-dependent RNA polymerase in plant antiviral defense - Xie, Zhixin (The National Academy of Sciences, 2001)
Plants contain RNA-dependent RNA polymerase (RdRP) activities that synthesize short cRNAs by using cellular or viral RNAs as templates. During studies of salicylic acid (SA)-induced resistance to viral pathogens, we recently found that the activity of a tobacco RdRP was increased in virus-infected or SA-treated plants. Biologically active SA analogs capable of activating plant defense response also induced the RdRP activity, whereas biologically inactive analogs did not. A tobacco RdRP gene, NtRDRP1, was isolated and found to be induced both by virus infection and by treatment with SA or its biologically active analogs. Tobacco lines deficient in the inducible RDRP activity were obtained by expressing antisense RNA for the NtRDRP1 gene in transgenic plants. When infected by tobacco mosaic virus, these transgenic plants accumulated significantly higher levels of viral RNA and developed more severe disease symptoms than wild-type plants. After infection by a strain of potato virus X that does not spread in wild-type tobacco plants, the transgenic NtRDRP1 antisense plants accumulated virus and developed symptoms not only locally in inoculated leaves but also systemically in upper uninoculated leaves. These results strongly suggest that inducible RdRP activity plays an important role in plant antiviral defense.